The literary writing of the city in México en 1554, by Francisco Cervantes de Salazar - Sanchis Amat, Víctor Manuel (2021)
The article analyzes the literary writing of Mexico City through the dialogues of Mexico in 1554, by Francisco Cervantes de Salazar, the first professor of rhetoric at the Royal and Pontifical University of Mexico. The objectives of the work intend to go through the different references that the chronicler builds on his walk through the viceregal capital and its link both with the tradition of the laudes civitatis, and with the writing of the topic of the locus amoenus that the humanists rescued during the Renaissance.